Tracer Study Berbasis Web SMA N 10 Muaro Jambi - Putri Fa'ainzani, Giffari Nuraulia; Zaenal Abidin, Dodo (Jurnal Manajemen Sistem Informasi, 2023)
SMA N 10 Muaro Jambi processes data on alumni activities after graduation, still in a manual way, namely by collecting alumni data directly at SMA N 10 Muaro Jambi. Alumni fill in alumni data into the alumni summary book; this data collection occurs when alumni legalize the diploma. After filling in the data, the TU staff then transfers the data that was filled earlier to the computer using Microsoft Excel as a medium for archiving data on alumni activities after graduation, recapping the results of the data that is made into a report and the report is printed every year. However, only some of the alumni data is captured, which results in errors or mistakes in writing alumni data in the alumni book and does not facilitate the process of searching for alumni data on a large scale if at any time the school needs data from an alumni from several years ago. The recording and management of alumni data is slow and difficult to realize. As for the purpose of this study, namely to analyze and study system problems that are currently running at SMA N 10 Muaro Jambi and system design in this study using UML (Unified Modeling Language) model tools such as use case diagrams, activity diagrams, and class diagrams, Furthermore, this study used the prototype system development method and used the Balsamiq Mockups 3 application tool as a design medium in producing a tracer study alumni information system user interface design at SMA N 10 Muaro Jambi. This research resulted in an alumni information system design that can process school profile data, alumni data, tracer study data, and other data so that it can present the required alumni report designs. The hope of what has been described in this research is that it can be a solution to existing problems as well as an illustration of or a good alumni information system design for alumni data collection at SMA N 10 Muaro Jambi.alumni information system for alumni data collection at SMA N 10 Muaro Jambi.